Prevalence And Molecular Characteristics Of Aeromonas Species Isolated From Fish, Shrimp And Waters - Noaman, Yousr Abdulhadi (2006)
Aeromonas species are ubiquitous aquatic micro-organisms which are opportunistic pathogens that have been associated to wound infections, gastroenteritis, septicemia, and traveler’s diarrhea in humans and hemorrhagic septicaemia in fish. The main routes of exposure in humans are ingestion of contaminated foods and drinking water, or direct contact with recreational waters. In this study, a total of 450 samples were obtained from different sources and locations in Malaysia. Two hundred fifty samples of fresh water were obtained from ponds in UPM (n=150) and in tiger prawn farm in Malacca (n=150), respectively. In addition, 100 samples of shrimps (Penaeus indicus) were purchased from different wet markets in Selangor state: Seri Kembangan (35), Kajang (35) and Bangi (30). Hundred samples of fish (Clarias batrachus) (n=50) and Tiger prawn (Penaeus monodon) (n=50) were obtained from UPM and tiger prawn farm in Malacca, respectively. 238 (52.8%) of the 450 samples were tested positive for the isolation of Aeromonas species, 49 (10.8% ), 43 (9.5%),33 (7.3%), 37 (8.4%), 25 (5.5%), 23 (5.1%), 19 (4.2%), 15 (3.3%) and 2% harbored A. veronii, A. allosacharophila, A. hydrophila, A. caviae, A. enterpelogenes, A. encheleia, A. trota, A. media like DNA and A. veronii biovar sobria, respectively. All the strains of A. hydrophila, A. caviae and A. veronii biovar sobria were tested for resistance to 15 antibiotics and 98.8% and 94.1% of the strains were resistant to amoxcillin and penicillin, respectively, followed by teicoplanin (89.4%), penicillin (81.1%) and 12.9% of the strains were found resistant to chloramphenicol. The Multiple Antibiotic Resistance Indexing (MAR) and the bionumeric analysis of A. hydrophila, A. caviae and A. veronii biovar sobria, showed that all of them originated from high-risk sources. Two molecular typing methods were used in this study to examine the intra/inter-specific genetic relatedness among the A. hydrophila, A. caviae and A. veronii biovar sobria strains. In the analysis by RAPD-PCR and ERIC-PCR, the size for RAPD and ERIC fragments ranged from 0.25 to 10.0 kb with an average number of sixteen and eight bands, respectively. Eighty five genotypes among the 85 A. hydrophila, A. caviae and A. veronii biovar sobria isolates were generated using RAPD and ERIC-PCR which indicated that the strains were very diverse. The PCR analysis for detection of aerolysin (aer) and hemolysin (hly) showed that 50.5% of the isolates carried hemolysin (hly) gene and 45.9% of the isolates carried aerolysin (aer) gene. The nucleotide blast results of aerolysin gene sequences representative A. hydrophila, A. caviae and A. veronii biovar sobria revealed a high homology of 94%, 95% and 95% for A. hydrophila, A. caviae and A. veronii biovar sobria published sequences, respectively. The protein blast also showed homology (97%, 94% and 96%) as compared with the Genbank database of National Centre for Biotechnology Information (NCBI). The present study demonstrates the high intra/inter-specific diversity within the Aeromonas species and reveals a clear differentiation of strains according to their ecological origin. Increasing presence of haemolysin-producing multiple antibiotic resistant A. hydrophila, A. caviae and A. veronii biovar sobria in food and environment may become a potential human health hazard. In conclusion, the research undertaken has contributed significantly to our knowledge of Aeromonas by providing new information on its distribution, its specific detection by PCR and inter/intra-species relationship.